1992
DOI: 10.1093/oxfordjournals.humrep.a137617
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of prednisolone/aspirin therapy for recurrent aborters with antiphospholipid antibody

Abstract: Seventeen women with recurrent fetal loss associated with anti-phospholipid antibody were treated by prednisolone and low-dose aspirin (PSL/ASP) therapy from the early gestational period. The success rate of pregnancy in the treated patients was significantly higher than that in 12 untreated patients of similar background, including age, number of previous fetal losses and anti-cardiolipin titre (76.5 versus 8.3%, P less than 0.01). The degree of fetal growth retardation evident in previous pregnancies was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 0 publications
0
38
0
Order By: Relevance
“…17 In addition, others found a reduction in fetal growth restriction in those treated with prednisolone compared with untreated women with obstetric APS. 7 High-dose steroid (40 mg) was used to suppress aPL titers and then tapered as antibody levels fell, but continued through pregnancy. 7 However, a randomized controlled trial that compared outcomes after treatment with aspirin plus prednisolone (40 mg) or a prophylactic dose of heparin demonstrated no difference in live birth rate but an increased frequency of preterm delivery because of premature rupture of membranes or preeclampsia in the group treated with prednisolone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 In addition, others found a reduction in fetal growth restriction in those treated with prednisolone compared with untreated women with obstetric APS. 7 High-dose steroid (40 mg) was used to suppress aPL titers and then tapered as antibody levels fell, but continued through pregnancy. 7 However, a randomized controlled trial that compared outcomes after treatment with aspirin plus prednisolone (40 mg) or a prophylactic dose of heparin demonstrated no difference in live birth rate but an increased frequency of preterm delivery because of premature rupture of membranes or preeclampsia in the group treated with prednisolone.…”
Section: Resultsmentioning
confidence: 99%
“…7 High-dose steroid (40 mg) was used to suppress aPL titers and then tapered as antibody levels fell, but continued through pregnancy. 7 However, a randomized controlled trial that compared outcomes after treatment with aspirin plus prednisolone (40 mg) or a prophylactic dose of heparin demonstrated no difference in live birth rate but an increased frequency of preterm delivery because of premature rupture of membranes or preeclampsia in the group treated with prednisolone. 8 Another randomized controlled trial in women with 2 or more first-trimester losses found no benefit in rates of fetal loss but increased preterm delivery in women treated with prednisolone (20 mg) plus aspirin compared with aspirin alone.…”
Section: Resultsmentioning
confidence: 99%
“…In four studies with early onset severe preeclampsia, 11.7% to 61% of women had significant levels of antiphospholipid antibodies (29)(30)(31)(32). In one study, the serum aCL levels were similar in patients with different grades of preeclampsia and women with normotensive pregnancies.…”
Section: Complications Of Apls In Pregnancymentioning
confidence: 98%
“…This variability may be explained by the lack of standardization of laboratory protocols (7)(8)(9) used to detect APAs (Table 2). Repeated testing of lupus anticoagulant (LA), anticardiolipin antibodies (IgG and IgM) showed a prevalence of persistent positive test results for APAs of approximately 15% (10,11). In contrast the prevalence of positive test results in unselected women is 3% to 5% and positive test results in asymptomatic women are not sensitive predictors of poor pregnancy outcome (12)(13)(14).…”
Section: Apls and Early Pregnancy Lossmentioning
confidence: 99%
“…It is important to note that, in recent prospective studies, women with RPL and aPL who refused to participate and remained untreated had successful pregnancies in less than 10% of cases [7,8].…”
mentioning
confidence: 99%